The Role of Parents in Shaping the Disciplined Character of Home Learning in Online Learning During the COVID-19 Pandemic: Peran Orangtua Dalam Membentuk Karakter Disiplin Belajar di Rumah Pada Pembelajaran Daring Selama Pandemi COVID-19F PARENTS IN FORMING THE CHARACTER OF HOME STUDYING DISCIPLINE IN ONLINE LEARNING DURING THE COVID19 PANDEMIC - Mellania Eka Febrianti; Feri Tirtoni (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the role of parents in shaping the disciplined character of studying at home during the covid19 pandemic and knowing about parental supervision when studying at home. This research is a qualitative research using an descriptive approach. The subjects in this research are parents of elementary school children. The results of this study indicate that the role of parents carries out two roles at once, the first to be a parent and the second to be a teacher at home; provide facilities that support children's learning spirit; supervising children's learning activities while at home; Supervise the good use of study time, as well as guide and encourage learning.